Engineering properties of crumb rubber modified dense-graded asphalt mixtures using dry process - Norhidayah, Abdul Hassan; Almusawi, Ali Abdulhussein Abdulridha; Mohd Zul Hanif, Mahmud; Nor Asniza, Mohamed Abdullah; Nurul Athma, Mohd Shukry; Nordiana, Mashros; Putra Jaya, Ramadhansyah; Nur Izzi, Md. Yusoff (IOP Publishing, 2019)
The development and production of high quality asphalt are crucial in the effort to meet current demands for the construction of roads. Crumb rubber is an industrial waste and one of the best ways to reduce the amount of this waste is by recycling it in the asphalt industry. Crumb rubber obtained from scrap tyres has been proven to be an effective additive for the modification of the properties of asphalt mixtures. This study presents a laboratory evaluation of the properties of crumb rubber modified asphalt mixture using the dry process method by adding three different sizes of crumb rubber, namely fine (≤1.18mm), coarse (≥1.18 but ≤3.35 mm), and combination of both fine and coarse (50/50), at three different percentages of crumb rubber, 0, 1.5 and 2.5% of the total weight of the aggregate. Crumb rubber was used to modify the dense graded mixture of asphaltic concrete wearing course 14 (ACWC14). The effect of crumb rubber in the mixture was investigated in terms of the volumetric properties using the Marshall Mix Design and mixture performance testing was conducted by means of resilient modulus, dynamic creep, and abrasion loss. Results showed that fine crumb rubber improved most of the properties of asphalt mixtures compared to other types of mixtures; this could be due to the partial interaction between rubber particles and bitumen which simultaneously act as an elastic aggregate in the mixture.